Stem cells research and its application : a review. - Mirzapour, Tooba; Tengku Ibrahim, Tengku Azmi; Movahedin, Mansoureh; Haron, Abd Wahid; Siraj, Siti Shapor; Koruji, Morteza; Nowroozi, Mohamadreza; Rafieian, Shahram (Science Alert, 2011)
Research in developmental biology has led to the discovery of different types of stem cells (totipotent, pluripotent and multipotent stem cells) that can give rise to multiple tissue types. This review summarizes a description about the stem cell concept, different type of stem cells and their potential applications. The face of extraordinary advances in the prevention, diagnosis and treatment of human diseases, devastating illnesses such as heart disease, diabetes, cancer and diseases of the nervous system, continue to deprive people of health, independence and well-being has been reviewed in this study. Stem cell research leading to prospective therapies in reparative medicine has the potential to affect the lives of millions of people around the world and there is a good reason to be optimistic. The road towards the development of an effective cell-based therapy for widespread use is long and involves overcoming numerous technical, legislative, ethical and safety issues.